Enhancing the piezoelectric performance of composite PVDF flexible films through optimizing β phase content, investigating additive effects, step‐wise polarization, and thermal pressing time for energy harvesting applications - Kamil Oflaz (21841958) (2024)
Polyvinylidene fluoride (PVDF), known for its piezoelectric versatility, emerges as a key contender for advancing efficient and sustainable energy harvesting in nanogenerators. This study explores the potential enhancement of piezoelectric properties in flexible PVDF polymers, employing a comprehensive approach through the solution casting method. The investigation integrates diverse additives, thermal treatments, and polarization methods to optimize performance, focusing on the impact of the β phase transition on electrical voltage generation. Utilizing the Taguchi experimental design, the study identifies optimal conditions for the composite PVDF film (OPT‐PVDF) through FT‐IR, XRD, and DSC analyses, with output voltage measurements confirming superior performance compared to pure PVDF (P‐PVDF). Specifically, BN‐doped PVDF films, with an 80% β phase content, achieve an impressive 6.48 V output voltage. This research underscores PVDF's potential for energy harvesting, emphasizing the pivotal role of optimizing β phase content, additive strategies, and the effects of polarization and thermal treatments. The study further evaluates the effect and necessity of subsequent thermal treatment and step‐wise polarization effects on the composite PVDF film material. The findings indicate that BN‐doped composite PVDF films, produced under optimal conditions, exhibit advanced piezoelectric properties. Other Information Published in: Journal of Applied Polymer Science License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1002/app.55530